Hepatological aspects of Epstein-Barr virus infection in children - Moppert, Justyna; Pawłowska, Małgorzata (Pediatria Polska - Polish Journal of Paediatrics, 2019)
The Epstein-Barr virus (EBV), belonging to the Herpesviridae family, is widespread in the world today. The most typical features of infectious mononucleosis include a triad of symptoms in the form of fever, cervical lymphadenopathy, and pharyngitis. Primary infection in the youngest children is usually asymptomatic and self-limiting. Hepatitis affects a significant proportion of patients and is usually a mild and self-limiting condition. Cholangitis is less common in the paediatric population and requires only symptomatic treatment in most cases. In contrast, in patients with immunodeficiency, EBV infection may be the cause of acute multiple organ failure and death. EBV infection plays an important and multifaceted role in the liver and biliary tract pathology due to its widespread distribution in the paediatric population.